EDUKASI PENGGUNAAN GADGET DENGAN BIJAK PADA ANAK USIA SEKOLAH DASAR - Nia Kurnia Asih; Nabil Mubarak, Enggar Arnelita Sari, Saydina Marsya, Muhammad Ridhai, Muhammad Rasyid Aluan Ridho, A (JOURNAL OF COMMUNITY DEDICATION, 2026)
The rapid development of digital technology has increased gadget usage among elementary school children, including those in Haruyan Dayak Village. Uncontrolled gadget use may negatively affect children’s social development, behavior, physical health, and emotional well-being. This activity aims to improve students’ understanding of wise gadget use through a Participatory Action Research (PAR) approach. The method includes problem identification, action planning, implementation of socialization activities, observation and evaluation, and reflection. The subjects were 30 students from grades 1 to 6 at SDN Haruyan Dayak. The results indicate that most students frequently use gadgets, primarily for entertainment such as social media, with limited understanding of healthy usage. The interactive socialization conducted through presentations, educational videos, and discussions successfully improved students’ understanding of the positive and negative impacts of gadgets, the importance of limiting screen time, and the productive use of gadgets. Additionally, initial behavioral changes were observed, such as reduced gadget use during class hours and increased awareness of the negative effects of excessive use. However, students’ understanding is not yet evenly distributed, indicating the need for continuous guidance from parents and teachers.